A SPECIAL FORM OF PROJECT TEACHING - NEUMANN, Karel (Trends in education, 2009)
The aim of this paper is to familiarize the readers with the issue of using imaginary and real firm in project teaching at secondary as well as basic schools. The paper also contains an account of the project teaching with regional features at basic schools which is being prepared now.
Keywords: Imaginary firm; real firm; project teaching; student company.